Life Expectancies of South African Adults Starting Antiretroviral Treatment: Collaborative Analysis of Cohort Studies - Johnson, Leigh F.; Mossong, Joel; Dorrington, Rob E.; Schomaker, Michael; Hoffmann, Christopher J.; Keiser, Olivia; Fox, Matthew P.; Wood, Robin; Prozesky, Hans; Giddy, Janet; Garone, Daniela Belen; Cornell, Morna; et al. (PLoS medicine, 2013)
Few estimates exist of the life expectancy of HIV-positive adults receiving antiretroviral treatment (ART) in low- and middle-income countries. We aimed to estimate the life expectancy of patients starting ART in South Africa and compare it with that of HIV-negative adults. Data were collected from six South African ART cohorts. Analysis was restricted to 37,740 HIV-positive adults starting ART for the first time. Estimates of mortality were obtained by linking patient records to the national population register. Relative survival models were used to estimate the excess mortality attributable to HIV by age, for different baseline CD4 categories and different durations. Non-HIV mortality was estimated using a South African demographic model. The average life expectancy of men starting ART varied between 27.6 y (95% CI: 25.2-30.2) at age 20 y and 10.1 y (95% CI: 9.3-10.8) at age 60 y, while estimates for women at the same ages were substantially higher, at 36.8 y (95% CI: 34.0-39.7) and 14.4 y (95% CI: 13.3-15.3), respectively. The life expectancy of a 20-y-old woman was 43.1 y (95% CI: 40.1-46.0) if her baseline CD4 count was ≥ 200 cells/µl, compared to 29.5 y (95% CI: 26.2-33.0) if her baseline CD4 count was <50 cells/µl. Life expectancies of patients with baseline CD4 counts ≥ 200 cells/µl were between 70% and 86% of those in HIV-negative adults of the same age and sex, and life expectancies were increased by 15%-20% in patients who had survived 2 y after starting ART. However, the analysis was limited by a lack of mortality data at longer durations. South African HIV-positive adults can have a near-normal life expectancy, provided that they start ART before their CD4 count drops below 200 cells/µl. These findings demonstrate that the near-normal life expectancies of HIV-positive individuals receiving ART in high-income countries can apply to low- and middle-income countries as well. Please see later in the article for the Editors' Summary.